VD_FINDINFO Jug / 2020 / 358 vom 29. Januar 2020 - VD Tribunal cantonal (2020)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉVISIONDÉCISION, DÉCISION D'IRRECEVABILITÉ, RÉCUSATION | 410 CPP (CH), 412 al. 2 CPP (CH), 60 CPP (CH)